Anemia and blood transfusion in children with septic shock: Does it affect outcome? A prospective observational study - Lalitha, A V; Joy, Shasta Theresa; Sumithra, S (Indian Journal of Child Health, 2018)
Background: Anemia is frequently encountered in critically ill children. Packed cell transfusion is a common therapeutic intervention in these children. The consequences of this on morbidity and mortality in children with septic shock are poorly defined and need to be explored. Objective: The objective of this study was to evaluate the prevalence of anemia and to explore the relationship of anemia and packed red blood cells transfusion to clinical outcomes in children with septic shock. Materials and Methods: A prospective observational study was conducted in a tertiary care hospital in pediatric intensive care unit between July 2013 and July 2014. Children between 1 month and 16 years of age with septic shock were enrolled in the study. The clinical profile including outcomes was noted in recruited patients. Results: The prevalence of anemia in children with septic shock was 63%. Among them, 13% were severely anemic. No significant differences were found in the Pediatric Risk of Mortality score, length of intensive care unit (ICU) stay, duration of inotropic requirement, hours of ventilation, and mortality rates between anemic and non-anemic children. Similar findings were observed between the transfused and non-transfused groups. However, the duration of inotropic requirement was longer among the transfused group (72 [6,120] vs. 48 [3, 72], p=0.025). A higher mortality rate was observed among transfused group with an odds ratio of 2.168 (95%, confidence interval [CI] 0.9–5) but was not statistically significant [p=0.08]. Conclusion: More than half of our children with septic shock were anemic at presentation. Anemia was not associated with increased mortality or morbidity. The transfused group had a higher mortality rate.